Characterization and butanol/ethanol sensing properties of mixed tungsten oxide and copper tungstate films obtained by spray-sol-gel - Damián, M. (2003)
Mixed WO3 – CuWO4 films have been prepared from aqueous solution of copper sulfate and polytungsten gel with molar ratio Cu/W from 0 to 100 %. These solutions were sprayed onto alumina substrates at 220 ºC. The obtained films were amorphous, and crystallized after an annealing at 300 °C in air for 3 h. The annealed films were composed by a mixture of CuWO4 and WO3 phases. The film obtained from a solution with an equimolar ratio of Cu/W was a pure CuWO4. The pure WO3 films obtained have a high surface “irregularities” (eventually the porosity). Those surface “irregularities” in the films were maintained or eventually increased as Cu/W molar ratio augments in the starting solution up to 10%. The gas sensitivities to butanol and ethanol vapors are also enhanced when the CuWO4 phase increases in the film up to 7% - 10%; further increments to this proportion the detection sensitivity decreases, so compromises are around 7% -10%. The gas sensitivity of pure CuWO4 was lower than pure WO3.